2000
DOI: 10.1097/00006123-200005000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Thermological Study of Drilling Bone Tissue with a High-speed Drill

Abstract: Intentional intermittent drilling with irrigation reduces temperature elevation and its expansion. These procedures are necessary for safe drilling, especially with a diamond burr. Although cold irrigation can minimize temperature elevation, its substantial effect on nerves or other structures needs to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(47 citation statements)
references
References 8 publications
1
45
0
1
Order By: Relevance
“…Performing anterior clinoidectomy causes potential complications owing to its deep location between the ICA and CN II and III. Injuries to CN II and III can be caused by unexpected motion of the drill or by heat caused by insufficient irrigation [28].In the present study, Type III pneumatization was detected in 29.9% of the males and 22.5% of the females. When ACP is pneumatized, there is relationship between ACP and sphenoid sinus.…”
supporting
confidence: 47%
See 1 more Smart Citation
“…Performing anterior clinoidectomy causes potential complications owing to its deep location between the ICA and CN II and III. Injuries to CN II and III can be caused by unexpected motion of the drill or by heat caused by insufficient irrigation [28].In the present study, Type III pneumatization was detected in 29.9% of the males and 22.5% of the females. When ACP is pneumatized, there is relationship between ACP and sphenoid sinus.…”
supporting
confidence: 47%
“…Performing anterior clinoidectomy causes potential complications owing to its deep location between the ICA and CN II and III. Injuries to CN II and III can be caused by unexpected motion of the drill or by heat caused by insufficient irrigation [28].…”
Section: Discussionmentioning
confidence: 99%
“…In orthopaedic surgery external irrigation with sterile saline delivered via a syringe or other device is routinely applied during drilling, the efficacy of which has been demonstrated by several authors (Matthews and Hirsch 1972;Jacob and Berry 1976;Lavelle and Wedgwood 1980;Krause, Bradbury et al 1982;Kondo, Okada et al 2000;Camargo, Faria et al 2007;Augustin, Davila et al 2008;Sener, Dergin et al 2009). Utilising a numerical model, Lee and co-workers (Lee, Rabin et al 2011) modelled the effect of coolant applied to the shank and exposed fluted portion of the operational drill-bit, demonstrating that this application may have a significant effect on the maximum drill temperature, even in the advanced stages of drilling where the cutting face is embedded deep in the bone.…”
Section: Intraoperative Temperature Abatement Strategiesmentioning
confidence: 99%
“…Sequential drilling at larger diameters is also performed to reduce maximal temperatures (Bubeck, Garcia-Lopez et al 2009). Intermittent drilling/burring has also been advocated as a means to reduce maximal temperature elevation (Kondo, Okada et al 2000).…”
Section: Intraoperative Temperature Abatement Strategiesmentioning
confidence: 99%
“…2,7) Experimental studies have shown that local heating may disturb the motor and sensory functions of nerve roots and sciatic nerves. 4,6,8,10) Various irrigation systems are now available for high-speed drills, 9) but experimental studies have shown that temperatures can still be elevated to hazardous levels, even if the operative surfaces are cooled by irrigation.…”
Section: Discussionmentioning
confidence: 99%